Psychosocial Support for Grade 3 Pupils Through Artistry in Music Featuring Ukulele Lesson - Amaro, Ailene D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The use of ukulele in school setting is becoming popular and its integration during classes is increasing in popularity. Because of this, it is significant and timely that this type of music be involved among learners of all ages. The consideration of providing support for mental and psychosocial well-being among the students during the past pandemic was deemed necessary. In this innovative work plan study, experimental-purposive approach was used in implementing the program. Integrating music in classes increases primary students' class involvement and engagement in school activities. Thus, the researcher introduced the Ukulele lesson to the Grade 3 pupils and tried to look into the effect of its integration to the pupils’ psychosocial development and academic performance. The participants were thirty-eight pupils (38) and eleven (11) MAPEH teachers for the school year 2022-2023 enrolled in an Integrated School in Pangasinan. The results revealed that there is an increase in the level of academic performance of the Grade 3 pupils who were exposed to ukulele lessons as an intervention program focusing on psychosocial support. The elementary teachers were also able to maintain classroom cohesiveness and increased pupils’ class participation. The noise from unnecessary talking and shouting or even playing inside the classroom were minimized. This is one proof that music is a great stress-relieving tool that helps to calm the mind and enhance concentration among pupils and teachers.